Anterior Cruciate Ligament Injuries in Australian Rules Football: Incidence, Prevention and Return to Play Outcomes - Webster, Kate E (Open Access J Sports Med, 2021)
Australian Rules football is the most popular of the various codes of football played in Australia. During the game players perform frequent landing, cutting and pivoting manoeuvres that expose them to substantial risk for anterior cruciate ligament (ACL) injury. Recent years have seen the introduction of a professional women’s league that has resulted in an exponential growth in the participation of women and girls in this sport. Unfortunately, there is a corresponding growth in ACL injury rates in female players. This review summarizes the incidence of ACL injury in both men’s and women’s Australian Rules football and reviews potential causative factors and risk reduction strategies. The final section takes an in depth look at return to sport outcomes after ACL reconstruction surgery in these populations. Whilst an ACL injury does not mean the end of a player’s career in Australian football, it certainly presents a significant challenge in terms of return to preinjury levels of form and high rates of secondary and tertiary ACL injury are also a significant concern.